An update on the role of psychotherapy in the management of bipolar disorder. - Miklowitz, D (2006)
Recent studies have examined the value of combining structured forms of psychotherapy with medication maintenance for patients with bipolar disorder. These studies have been influenced by the growing body of literature on stress in the elicitation of manic and depressive episodes. Randomized trials published within the past 5 years indicate positive benefits of cognitive-behavioral therapy, interpersonal and social rhythm therapy, family-focused therapy, and group psychoeducation as adjuncts to mood stabilizers in delaying recurrences, stabilizing symptoms, and improving medication adherence. Open trials of family interventions for pediatric-onset bipolar patients also have yielded promising results. Questions remain about the relative advantages of one psychosocial approach over the others, whether there are subgroups of patients who respond to each type of intervention, the impact of psychotherapy on role functioning, mediators of treatment effects, and the potential utility of early intervention as a means of delaying the onset and/or severity of the disorder.